Hubungan Antara Strategi Konten, Desain Kreatif, Pemilihan Caption, dan Hashtag Terhadap Minat Berdonasi di BAZNAS Kalimantan Timur - Ahmad Fahrurozy; Aminah Nuriyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Instagram has emerged as a vital platform for non-profit organizations, including the National Zakat Agency (BAZNAS) of East Kalimantan, facilitating communication and fundraising efforts for Zakat, Infaq, and Sedekah (ZIS). However, there is limited understanding of the specific factors influencing audience donation interest on this platform. This study aims to analyze the relationship between content strategy, creative design, caption selection, hashtag usage, and the donation interest among followers of the BAZNAS East Kalimantan Instagram account (@baznaskaltim). Employing a quantitative approach with a survey method, data were collected via questionnaires from 116 respondents. These respondents were active followers who had interacted (liked or commented) within the past 90 days, selected through purposive sampling. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that content strategy, creative design, caption selection, and hashtag usage significantly positively influence donation interest. Creative design was identified as the factor with the strongest influence. In conclusion, digital communication elements on Instagram play a crucial role in enhancing donation interest. Optimizing these elements, particularly visual aspects, is recommended to improve the effectiveness of BAZNAS East Kalimantan's donation campaigns.